Research Progress on Health Benefits and Implementation Strategies of Dietary Methionine Restriction - LU Manman, QIAN Jing, YANG Yuhui, XIE Yanli, LE Guowei (Shipin Kexue, 2023)
Methionine is the only essential sulfur-containing amino acid required for the human body and is involved in important metabolic pathways including protein synthesis, transsulfuration, and one-carbon metabolism. However, in recent years, a large number of studies have shown that restricting dietary methionine intake exerts many physiological functions beneficial to body health. This article comprehensively summarizes the benefits of methionine restriction (MR) including promoting gut health, prolonging lifespan, reducing lipid accumulation and body mass, increasing insulin sensitivity, ameliorating diabetes, atherosclerosis and other cardiovascular diseases, improving learning and memory function, and anti-tumor and anti-cancer effects, as well as the effects of MR on bone and skeletal muscle function and protein synthesis. In addition, the strengths and weaknesses of five MR strategies including protein-restriction diet, vegan diet, diet formulation based on monomeric amino acid, oral methioninase, and injection of recombinant methioninase are reviewed in this article. It also discusses future major research directions, which may provide a theoretical reference for the development and application of new foods containing low levels of methionine and the realization of the health functions of MR.